Study of Evaporation Performance Between Centrifugal Spray Evaporation and Bypass Flue Evaporation to Treat Desulfurization Wastewater - Ning ZHAO; Yongxin FENG; Tingkun LIN; Qingshan YANG; Zhiwen XIE (Zhongguo dianli)
To investigate the high-temperature bypass flue gas evaporation technologies including centrifugal spray evaporation tower and bypass flue evaporation, spray evaporation experiments were conducted using desulfurization wastewater. Evaporation process of wastewater droplets was revealed by the fluorescent tracer technique and single droplet evaporation characteristics. The influences of inlet temperature and residence time on the evaporation efficiency were also discussed. Differences between the two wastewater treatment technologies were analyzed. The results show that after being exposed to the hot flue gas, desulfurization wastewater droplets would rapidly lose their free water, form shells and turn into semi-dried particles, with temperature in the main evaporation zone of the dryer decreasing significantly. Increasing inlet temperature helps to improve the evaporation rate and reduce the moisture content of the outlet ash particles. By increasing the size of the dryers and controlling the amount of extracted flue gas, the residence time of high temperature flue gas in dryers can be extended, which is about to improve the heat utilization and achieve the drying effect with low gas-liquid ratio. In comparison with the bypass flue evaporation technique, centrifugal spray evaporation tower was better due to better atomization performance and uniform gas-liquid mixing.